Beginning Silverlight 5 in C# - Lair, Robert. (Apress : Imprint: Apress, 2012)
The growing popularity of Web 2.0 applications is increasing user expectations for high-quality website design, presentation, and functionality. It is into this climate that Microsoft is releasing Silverlight 5, the latest iteration of its cross-browser web presentation technology. Beginning Silverlight 5 in C# brings you to the cutting edge of Web 2.0 application design and includes plenty of practical guidance to get you started straight away. Silverlight design tools have important differences compared with those used to create Ajax and JavaScript functionality. Robert Lair takes you on a tour of all the tools, including: Microsoft Expression Design, which plays an important role in creating Silverlight assets Microsoft Expression Blend, which is used to build user interaction for Silverlight elements Microsoft Visual Studio, which manages the interaction between designers and developers, providing the coding environment for "nuts and bolts" wiring Once you’ve mastered the basics, you'll move on to gain a more in-depth knowledge of some of the features introduced with Silverlight 5, including H.264 protected content, right-click event handling, a new printing API, and support for the Managed Extensibility Framework.